Public views on healthcare performance indicators and patient choice. - Magee, H; Davis, L; Coulter, A (2003)
Patients on certain waiting lists in the UK National Health Service (NHS) are now offered the choice of persevering with their home hospital or switching to another hospital where they will be treated on a guaranteed date. Such decisions require knowledge of performance. We used facilitated focus groups to investigate the views of patients and members of the public on publication of information about the performance of healthcare providers. Six groups with a total of 50 participants met in six different locations in England. Participants felt that independent monitoring of healthcare performance is necessary, but they were ambivalent about the value of performance indicators and hospital rankings. They tended to distrust government information and preferred the presentational style of 'Dr Foster', a commercial information provider, because it gave more detailed locally relevant information. Many participants felt the NHS did not offer much scope for choice of provider. If public access to performance information is to succeed in informing referral decisions and raising quality standards, the public and general practitioners will need education on how to interpret and use the data.